The Effect of Tax Knowledge and Tax Sanctions on Business Entity Taxpayer Compliance - Oktariyana, Made Denny (P3M- Politeknik Negeri Kupang, 2022)
Tax is one of the state revenues for state development. The Directorate General of Taxes for the Kupang Region seeks to increase the level of tax revenue through taxpayers. The city of Kupang itself still has several agencies or companies that are low in taxpayer compliance. This type of research uses quantitative research using primary data and secondary data. Sampling using incidental sampling technique with 100 respondents. Methods of data collection using a questionnaire. The data analysis technique used is the classical assumption test and hypothesis testing. Tax is one of the state revenues for state development. The Directorate General of Taxes for the Kupang Region seeks to increase the level of tax revenue through taxpayers. The city of Kupang itself still has several agencies or companies that are low in taxpayer compliance. This type of research uses quantitative research using primary data and secondary data. The sample technique used is simple random sampling with the calculation of the solvin formula that gets a sample of 100. Methods of data collection using a questionnaire. The data analysis technique used was classical assumption test and hypothesis testing. The results of this study indicate that tax knowledge and tax sanctions have a positive effect on taxpayer compliance.